2020
DOI: 10.3390/ijerph17031101
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Serum HDL-C Level Is Associated with Elevation of Blood Pressure: Correlation Analysis from the Korean National Health and Nutrition Examination Survey 2017

Abstract: A low-serum, high-density lipoproteins-cholesterol (HDL-C) level and high blood pressure (BP) are independent risk factors for cardiovascular disease and dementia. In the present study, in order to find putative correlation between low HDL-C and hypertension, 4552 subjects (20-80 years old) were selected from the Korean National Health And Nutrition Examination Survey 2017 (KNHANES VII-2, n = 2017 men, n = 2535 women). They were classified into four levels of blood pressure, ranging from BP1 (normal, below 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
8
23
1
Order By: Relevance
“…Keeping BMI as low as possible in the normal range is an effective way to prevent or attenuate the development of HDL-C hypolipidemia. Consistent with the present results, Cho et al [ 46 ] also found an association between declining serum HDL-C and blood pressure and HDL-C hypolipidemia. This study also illustrated that HDL-C level in the baseline year had the greatest impact on the incidence of HDL-C hypolipidemia among all biological indicators, with HR only equal to 0.002.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Keeping BMI as low as possible in the normal range is an effective way to prevent or attenuate the development of HDL-C hypolipidemia. Consistent with the present results, Cho et al [ 46 ] also found an association between declining serum HDL-C and blood pressure and HDL-C hypolipidemia. This study also illustrated that HDL-C level in the baseline year had the greatest impact on the incidence of HDL-C hypolipidemia among all biological indicators, with HR only equal to 0.002.…”
Section: Discussionsupporting
confidence: 93%
“…One reason was that previous samples comprised the entire population, while patients with metabolic diseases in this study were screened out in the baseline year. Males were 1.258 times as likely to have HDL-C hypolipidemia as females, which is different from the results of cross-sectional studies [ 46 – 50 ]. There are two possible reasons.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Previous studies performed in Korea investigated the accuracy of limited numbers of equations for LDL cal [ 8 , 14 , 18 ]. In Korea, LDL Friedewald is most commonly used for LDL cal [ 8 , 24 ]. Therefore, the aim of this study was to evaluate the performance of a new LDL equation (LDL Choi ) along with previous LDL estimations using 11 equations for LDL calculation in comparison with directly measured LDL in Korean adults to improve understanding of LDL calculations when direct measurement is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…The average American man expects to live to 76 years of age, whereas the average woman in America expects to live to 81 years of age [27]. One possible explanation might be that the lowered HDL-C level is associated with a higher prevalence of hypertension [28] and cardiovascular events, and a lower HDL-C pattern contributes to men's elevated rates of coronary heart disease and mortality [29]. Quantity and quality of HDL are very important to suppress the incidence of metabolic disease and they could be impaired by ageing and an unhealthy lifestyle [30].…”
Section: Discussionmentioning
confidence: 99%